Using reduced graphene oxide to remove lead from the Environment - Jehan Adnan Abed; hazim abed walli Walli (Al-Qadisiyah Journal of Pure Science, 2020)
AbstractThe current study aims to evaluate the adsorption process of the lead element in aqueous solution by means of nanomaterial (reduced graphene oxide) that was prepared from the reduction of graphene oxide GO prepared by the Hummers method “nanomaterial was diagnosed (rGO) and to study its properties and characteristics by means of a scanning electron microscope (SEM) and a microscope. Atomic force (AFM). results showed that the percentage of removal of the element increased with increasing time, and as the results recorded that The highest adsorption was at a concentration of 100 mg  of elemental lead. This indicates that the removal rate decreases with increasing the initial concentration of the adsorbent